BLUEGENIC: Transforming marine plastic waste through AI drone surveillance as a solution for sustainable energy and maritime security - Sendi Kurnia Putra; Nur Hafifa (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The issue of marine plastic waste has become a tangible threat to the sustainability of marine ecosystems and national maritime security. This study aims to develop BLUEGENIC, a technology-based innovation that integrates marine surveillance using artificial intelligence (AI)-powered drones with the conversion of plastic waste into alternative fuel. Methods: The research employed a Research and Development (R&D) approach through several stages, including needs analysis, system design, concept testing, and validation of implementation potential. Findings: The results indicate that the routine deployment of AI drones in priority maritime areas can map between 50–200 tons of marine plastic waste annually. The collected waste is then processed using the pyrolysis method, capable of producing 13,000–14,000 liters of alternative fuel per month from approximately 16.7 tons of plastic. In addition to contributing to waste reduction and clean energy transition, BLUEGENIC engages the younger maritime generation in research, education, and technological operations. Conclusion: The program also demonstrates economic potential through a blue economy approach and offers opportunities for cross-sectoral collaboration. This study emphasizes the importance of regulatory support and stakeholder synergy in the implementation of BLUEGENIC. Novelty/Originality of this article: The novelty lies in the synergy between AI-drone technology and plastic waste–based alternative energy within the framework of sustainable ocean management and the empowerment of young human resources in the maritime sector.